Linkage-specific conformational ensembles of non-canonical polyubiquitin chains. Issue 8 (30th September 2015) - Castañeda, Carlos A.; Chaturvedi, Apurva; Camara, Christina M.; Curtis, Joseph E.; Krueger, Susan; Fushman, David
Abstract : Ensemble analysis using NMR and SANS revealed conformational heterogeneity of polyubiquitin chains, suggesting unique as well as overlapping functions. Abstract : Polyubiquitination is a critical protein post-translational modification involved in a variety of processes in eukaryotic cells. The molecular basis for selective recognition of the polyubiquitin signals by cellular receptors is determined by the conformations polyubiquitin chains adopt; this has been demonstrated for K48- and K63-linked chains. Recent studies of the so-called non-canonical chains (linked via K6, K11, K27, K29, or K33) suggest they play important regulatory roles in growth, development, and immune system pathways, but biophysical studies are needed to elucidate the physical/structural basis of their interactions with receptors. A first step towards this goal is characterization of the conformations these chains adopt in solution. We assembled diubiquitins (Ub2 ) comprised of every lysine linkage. Using solution NMR measurements, small-angle neutron scattering (SANS), and in silico ensemble generation, we determined population-weighted conformational ensembles that shed light on the structure and dynamics of the non-canonical polyubiquitin chains. We found that polyubiquitin is conformationally heterogeneous, and each chain type exhibits unique conformational ensembles. For example, K6-Ub2 and K11-Ub2 (at physiological salt concentration) are in dynamic equilibrium between at least two conformers, where one exhibits a unique Ub/Ub interface, distinct from that observed in K48-Ub2 but similar to crystal structures of these chains. Conformers for K29-Ub2 and K33-Ub2 resemble recent crystal structures in the ligand-bound state. Remarkably, a number of diubiquitins adopt conformers similar to K48-Ub2 or K63-Ub2, suggesting potential overlap of biological function among different lysine linkages. These studies highlight the potential power of determining function from elucidation of conformational states.